Pathogen determination from clinical abscess fluids using metagenomic next-generation sequencing - Zhao, Yuxi; Chen, Jinlian; Bai, Bing; Wang, Yu; Zheng, Jinxin; Yu, Zhijian; Deng, Qiwen; Li, Peiyu (Folia microbiologica, 2021)
Abscesses are often clinically manifested as local necrotic tissues in various organs or systems of the human body, which is commonly caused by microbial infection. Rapid and accurate identification of pathogens from clinical abscetic samples would greatly guide a clinician to make the precise choices of the antimicrobial treatment. Here, this study aimed to investigate the application of metagenomic next-generation sequencing (mNGS) in the microbial detection of clinical samples of abscess fluids from various organs or systems. Nine patients with abscess from various organs or systems were enrolled in this study. The pathogenic bacteria in abscess fluid were detected and compared by the conventional bacterial culture and mNGS respectively. The dominant pathogens of abscess fluids in 8 cases can be found directly from mNGS, dominating over 80% of the total reads abundance of the microbiome. Although the pathogens from 6 cases detected by mNGS were consistent with that from the conventional bacteria culture method, the fastidious obligate anaerobic bacteria in 2 cases additionally detected by mNGS were not found by the conventional culture method. Moreover, complex polymicrobial infection containing Parvimonas micra in one case negatively with conventional bacterial culture were demonstrated by the mNGS method. And the mNGS method can directly reflect the diversity of microbial ecology in the abscess fluids from the different parts of the human body. Conclusively, mNGS can be used as a supplemental method for the pathogen detection of clinically abscess fluids.
Keywords: Abscess; vysoce účinné nukleotidové sekvenování; High-Throughput Nucleotide Sequencing; metagenomika; Sensitivity and Specificity; senzitivita a specificita; Humans; absces; Metagenomics; lidé; Firmicutes